Belize : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper assesses the current strength of the balance sheets of large banks in Belize and takes stock of progress made on the regulatory, supervisory, and crisis management frameworks since the 2011 Financial Sector Assessment Program (FSAP). The improvement in financial stability indicators was boosted by implementation of key FSAP recommendations. The Central Bank strengthened provisioning and loan classification standards. The new rules force banks to focus more on the borrower's capacity to repay the loan rather than on the value of collaterals. The regulatory, supervisory, and crisis management frameworks as well as the financial infrastructure could be further strengthened. The supervision department of the Central Bank could be strengthened with examiners specializing in information technologies (IT) with the view of ensuring the integrity of banks' IT systems. Asset quality reviews and forward-looking stress tests could complement current supervisory practices and improve Central Bank's assessments of banks' balance sheets.